Prevalence and associated factors of epiretinal membrane using spectralis OCT in Fujian Eye Study - Li, Yang; Li, Xiaoxin; Hu, Yonghua; Wang, Bin; Zhang, Mingqin; Hu, Qinrui (Scientific reports, 2025)
We aimed to determine the prevalence and risk factors of epiretinal membrane in a population-based study of residents aged 50 years and older in Fujian Province, Southeast China. The Fujian Eye Study is a population-based cross-sectional eye study in Fujian province, Southeast China. Residents aged 50 years and older were enrolled and did the questionnaire (educational background, income, blood type, disease history, medication history, smoking, drinking and tea consumption, et al.), physical and ophthalmological examinations with height, weight, systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), refraction, intraocular pressure (IOP), slit lamp, nonmydriatic fundus photograph and spectralis optical coherence tomography (OCT) imaging. Nonmydriatic fundus photograph and Spectralis OCT were used to assess ERM according to a standardised protocol. A total of 8173 residents were included in this study. Among them, 8.42% (95% CI 0.0782–0.0902) had ERM in at least one eye. Multiple logistic regression showed the presence of ERM was only associated with urbanization and geographic location, but not with age, sex, refractive error, IOP, SBP, DBP, HR, BMI, hypertension, diabetic mellitus, hyperlipidemia, education, income, smoking, alcohol and tea consumption. ERM is common among Chinese with 8.42% in at least one eye. Urbanization and geographic location are the only associated factors for ERM in Fujian Eye Study.